Macroinvertebrate Recovery to Varying Hydropeaking Frequency: A Small Hydropower Plant Experiment - Aksamit, Claire Kathryn; Carolli, Mauro; Vanzo, Davide; Weber, Christine; Schmid, Martin (Frontiers in Environmental Science, 2021)
As the demand for hydroelectricity progresses worldwide, small hydropower operators are increasingly examining the feasibility of using existing infrastructure (e.g., settling basins) in run-of-the-river schemes for intermittent power production. Such flexible production causes short-term discharge fluctuations (hydropeaking) in downstream reaches with potential adverse effects for the sensitive fauna and flora in alpine streams. In an experimental field study on a previously unregulated section of the upper Rhone River (Switzerland), we measured density and composition of macroinvertebrate drift in two habitats (riffle, pool) following a 15-minute hydropeaking wave. The experimental hydropeaking was replicated five times over 14 days with decreasing recovery times between peaks (8, 3, 2 days, and 24 h), and drift measurements were compared with kick samples for the benthic community. Results from the kick sampling showed that benthic macroinvertebrate abundance and composition did not significantly change between the experimental peaks. There were habitat specific reactions in macroinvertebrate drift to hydropeaking, with the pool experiencing more pronounced drift abundances than the riffle. Overall, drift abundance was not significantly correlated with recovery time, but results indicate taxa-specific differences. This research advocates for the importance of completing more in-situ field experiments in order to better understand the ecological impact of flexible power production in small hydropower plants.